The Impacts of Hinged and Solid Ankle-Foot Orthoses on Standing and Walking in Children with Spastic Diplegia - DALVAND, Hamid; DEHGHAN, Leila; FEIZI, Awat; HOSSEINI, Seyed Ali; AMIRSALARI, Suzan (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Dalvand H, Dehghan L, Feizi A, Hosseini SA, Amirsalari S. Iran J Child Neurol. 2013 Autumn; 7(4):12-19. Abstract Objective The purpose of this study was to examine the impacts of hinged and solid anklefoot orthoses (AFOs) on standing and walking abilities in children with spastic diplegia. Materials & Methods In a quasi-experimental design, 30 children with spastic diplegia, aged 4-6 years were recruited. They were matched in terms of age, IQ, and level of GMFCS E&R. Children were randomly assigned into 3 groups: a hinged AFO group (n=10) plus occupational therapy (OT), a solid AFO group (n=10) plus OT, a control group who used only OT for three months. Gross motor abilities were measured using Gross Motor Measure Function (GMFM). Results We obtained statistically significant differences in the values between baseline and after treatment in all groups. The groups were also significantly different in total GMFM after intervention. Furthermore, there were differences between hinged AFOs and solid AFOs groups, and between hinged AFOs and control groups. Conclusion We concluded that gross motor function was improved in all groups; however, hinged AFOs group appears to improve the gross motor function better than solid AFOs and control groups. References Miller F. Cerebral palsy. 1st ed. New York: Springer Science & Business Media; 2005. Wren TL, Rethlefsen S, Kay RM. Prevalence of specific gait abnormalities in children with cerebral palsy: Influence of cerebral palsy subtype, age, and previous surgery. J Pediat Orthoped 2005;25(1):79-83. Knutosn L, Clark D. Orthotic devices for ambulation in children with cerebral palsy and myelomeningocele. Phys Ther 1991;71:947-60. Figueiredo EM, Ferreira GB, Maia Moreira RC, Kirkwood R, Fetters L. Efficacy of Ankle-Foot Orthoses on Gait of Children with Cerebral Palsy: Systematic Review of Literature. Pediat Phys Ther 2008; 20(3):207-23. Brehm MA, Harlaar J, Schwartz M. Effect of ankle-foot orthoses on walking efficiency and gait in children with cerebral palsy. J Rehabil Med 2008;40(7):529-34. Abel MF, Juhl GA,Vaughan CL, Damiano DL. Gait assessment of fixed ankle-foot orthoses in children with spastic diplegia. Arch Phys Med Rehabil 1998;79(2):126-33. Balaban B, Yasar E, Dal U, Yazicioglu K, Mohur H, Kalyon TA. The effect of hinged ankle-foot orthosis on gait and energy expenditure in spastic hemiplegic cerebral palsy. Disabil Rehabil 2007;29(2):139-44. Wilson H, Haideri N, Song K, Telford D. Ankle-foot orthoses for preambulatory children with spastic diplegia. J Pediat Orthoped 1997;17(3):370-6. Romkes J, Hell AK, Brunner R. Changes in muscle activity in children with hemiplegic cerebral palsy while walking with and without ankle-foot orthoses. Gait Posture 2006;24(4):467-74. Radtka SA, Skinner SR, Dixon DM, Johanson ME. A comparison of gait with solid, dynamic, and no ankle-foot orthoses in children with spastic cerebral palsy. Phys Ther 1997;77(4):395-409. Radtka SA, Skinner SR, Johanson ME. A comparison of gait with solid and hinged ankle-foot orthoses in children with spastic diplegic cerebral palsy. Gait Posture 2005;21:303-10. Hayek S, Hemo Y, Chamis S, Bat R, Segev E, Wientroub S, et al. The effect of community prescribed ankle–foot orthoses on gait parameters in children with spastic cerebral palsy. J Children’s Orthoped 2007;1(6):325-32. Burtenr PA, Woollactt MM, Qualls C. Stance balance control with orthoses in a group of children with spastic cerebral palsy. Dev Med Child Neurol 1999;41(11):748-57. Bjornson KF, Schmale GA, Adamczyk-Foster A, McLaughlin J. The effect of dynamic ankle foot orthoses on function in children with cerebral palsy. J Pediat Orthoped 2006;26(6):773-6. Hassani S, Ferdjallah M, Reiners K, Johnson C, Smith P, Harris G. Motor performance comparison of the hinged and dynamic ankle-foot orthotics. Dev Med Child Neurol 2002;44(91):4. Smith PA, Hassani S, Graf A, Flanagan A, Reiners K. Brace evaluation in children with diplegic cerebral palsy with a jump gait pattern. J Bone Joint Surg Am 2009;91(2):356-65. Zhang J, Wang Y, Yang Z. Comparison of dynamic and solid ankle-foot orthosis configurations for cerebral palsy children with spastic diplegia. Chine J Rehabil Med 2009;24(1):45-8. Case Smith J. Occupational therapy for children. 5th ed. Michigan: Elsevier Mosby; 2005. Palisano R, Rosenbaum P, Walter S, Russell D, Wood E, Galuppi B. Development and reliability of a system to classify gross motor function in children with cerebral palsy. Dev Med Child Neurol 1997; 39(4):214–23. Wood E, Rosenbaum P. The gross motor function classification system for cerebral palsy: a study of reliability and stability over time. Dev Med Child Neurol 2000;42(5):292-6. Dehghan L, Dalvand H, Abdolvahab M, Bagheri H, Faghih zade S. Inter rater reliability of Persian version Gross Motor Function Classification System Expanded & Revised in patients with cerebral palsy. Bimonthly Official Publication Medical Daneshvar 2011;18(91):2-8. Russell DJ, Rosenbaum PL, Avery LM, Lane M. Gross Motor Function Measure (GMFM’66&GMFM’88) user’s manual. 1st ed: London; Mac Keith Press; 2002. Russell DJ, Goster JW. Assessing functional differences in gross motor skills in children with cerebral palsy who use an ambulatory aid or orthoses: can the GMFM-88 help? Dev Med Child Neurol 2005;47(7):462-7. Drouin LM, Malouin F, Richards CL, Marcoux S. Correlation between the gross motor function measure scores and gait spatiotemporal measures in children with neurological impairments. Dev Med Child Neurol 1996;38(11):1007-19. Buckon CE, Thomas SS, Jakobson-Huston S, Sussman M, Aiona M. Comparison of three ankle-foot orthosis configurations for children with spastic hemiplegia. Dev Med Child Neurol 2001;43(6):371-8. Middleton EA, Hurley GRB, McIlwain JS. The role of rigid and hinged polypropylene ankle-foot-orthoses in the management of cerebral palsy: A case study. Prosthetics and Orthotics International 1988;12(3):129-35. Rethlefsen S, Kay R, Dennis S, Forstein M, Tolo V. The effects of fixed and articulated ankle-foot orthoses on gait patterns in subjects with cerebral palsy. J Pediat Orthoped 1999;19(4):470-4. Neumann DA. Kinesiology of the musculoskeletal system foundations for physical rehabilitation. 1st ed. Michigan: Mosby; 2002. Buckon CE, Thomas SS, Jakobson-Huston S, Moor M, Sussman M, Aiona M. Comparison of three ankle-foot orthosis configurations for children with spastic diplegia. Dev Med Child Neurol 2004;46(9):590-8. Rodda JM, Graham HK, Carson L, Galea MP, Wolfe R. Sagittal gait patterns in spastic diplegia. J Bone Joint Surg Br 2004;86(2):251-8.